Peningkatan kompetensi pengelolaan sistem operasi Linux Red Hat di SMK Muhammadiyah 2 Sukoharjo - Yudanto, Bramasto Wiryawan; Kustanto, Kustanto (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2025)
The increasing need for information systems at this time also coincides with the demand for reliable server infrastructure provider services, in order to produce maximum Information Technology services, IT human resources are needed who are able to manage server infrastructure optimally (Sirait, 2018). The vocational school educational institution with the TKJ major currently produces graduates who have an impact on fulfilling human resources in the field of IT services. The current level of mastery of the latest Linux technology which is still low in vocational school institutions majoring in TKJ can have an impact on the quality of skills possessed by vocational school graduates, therefore up-to-date Linux learning resources are needed so that vocational school graduates have competencies that are in line with the needs of the current IT industry.